2023
DOI: 10.3390/healthcare11192668
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Exercise on Cardiovascular Autonomic Nervous Function in Patients with Diabetes: A Systematic Review

Hidetaka Hamasaki

Abstract: Background: Diabetic neuropathy, including autonomic neuropathy, is a severe complication in patients with poorly controlled diabetes. Specifically, cardiovascular autonomic neuropathy (CAN) plays a significant prognostic role in cardiovascular morbidity and mortality. Exercise, an essential component of diabetes treatment, may have a therapeutic effect on patients with diabetes complicated by CAN. However, it remains unclear whether exercise has a therapeutic or protective effect in diabetes patients with CAN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…It is a nonspecific predictor of mortality which reflects central-autonomic moment-to-moment adaption of somatic responses and emotional appraisal to maintain homeostasis and adapt to environmental stimuli [ 42 ]. In the context of diabetes, detection of a low HRV through measures such as MCR should prompt consideration of improved lifestyle factors including exercise [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is a nonspecific predictor of mortality which reflects central-autonomic moment-to-moment adaption of somatic responses and emotional appraisal to maintain homeostasis and adapt to environmental stimuli [ 42 ]. In the context of diabetes, detection of a low HRV through measures such as MCR should prompt consideration of improved lifestyle factors including exercise [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The autonomic nervous system is divided into the sympathetic and parasympathetic nervous systems. The sympathetic nervous system responds to stress by accelerating HR and raising BP, whereas the parasympathetic nervous system helps the body rest and digest, slowing down the HR [ 3 ]. Dysregulation in these systems can lead to various cardiovascular issues, including decreased heart rate variability (HRV) and orthostatic hypotension.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review reported that T2DM was associated with a decrease in parasympathetic activity, as indicated by RMSSD, while findings regarding sympathetic activity, as indicated by the LF/HF ratio, were inconclusive [7]. A previous systematic review reported that exercise, encompassing aerobic exercise combined with resistance training, high-intensity interval training, and progressive resistance training, had a positive impact on cardiac autonomic function in individuals with T2DM [16]. Additionally, a previous systematic meta-analysis reported a lower RMSSD but no change in the LF/HF ratio in T2DM patients compared to healthy participants [7].…”
Section: Introductionmentioning
confidence: 99%